Analysis of Maqasid Sharia Values in the Management of Waqf Land and Buildings: A Case Study of the AS-Sanusy Prayer Hall for Community Empowerment - Muhammad Burhanudin Yahya; Moch. Khoirul Anwar; Ramdani R; Taufiq Kurniawan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
This study aims to analyze the application of maqasid shariah values in the management of the waqf of land and building of Mushola As-Sanusy in Surabaya City and its implications for community empowerment. The maqasid shariah approach is used as an analytical framework to assess the extent to which waqf management can realize substantive public benefit, not limited to legal-formal aspects. This study uses a qualitative approach with a case study design. Data collection techniques were carried out through in-depth interviews, observation, and documentation. The research subjects consisted of the donor’s family, the mushola’s administrators, and the congregation. Data analysis was conducted using an interactive analysis model that includes data reduction, data presentation, and drawing conclusions. The results show that the waqf management of Mushola As-Sanusy has applied maqasid shariah values through worship activities, religious education, and social community activities. However, waqf utilization still tends to be consumptive, so the development of productive waqf becomes a strategic need to strengthen the hifz al-mal aspect and the economic empowerment of the community.